Disputed Nature and Property: Socio-Environmental Conflicts in the Matanza-Riachuelo Basin, Argentina (1960–2020) - Dichdji, Ayelen (2025)
This article explores the relationship between environmental degradation and urban land property dynamics in the Matanza-Riachuelo Basin (Argentina) between 1960 and 2020. Using a historical-socioenvironmental approach, it examines how chronic pollution, informal urbanization, and grassroots collective action have redefined the boundaries between legal and illegal land tenure. Drawing on oral histories, documents, and media analysis, the study reconstructs local struggles for land legalization, the role of the State, and the influence of environmental movements in bringing visibility to the crisis. It argues that urban property in the basin cannot be understood apart from the socio-environmental conflicts that challenge legal frameworks and produce new, bottom-up forms of territorial legitimacy.